Do the Characteristics of Internal Audits and Compliance Functions Affect Sharia Compliance? - Laili Latifah Puspitasari; Wuri Handayani (Journal of Indonesian Economy and Business (JIEB), 2020)
Introduction: This study aims to explore the relationship between the characteristics of an internal audit (IA) and a compliance function (CF) toward sharia compliance. Background Problems: The Sharia Supervisory Board (SSB), which is supposed to guarantee sharia compliance in Islamic banking, does not function properly. Consequently, the SSB delegates this supervision to the banks’ employees, so the compliance function and internal audit become common practices used to address any issues. Novelty: The majority of previous studies have examined the role/characteristics of the SSB in sharia compliance. On the other hand, few studies have examined the role/characteristics of IA and CF in sharia compliance. Therefore, this study was conducted to examine the characteristics of IA and CF toward sharia compliance. Research Method: The study utilized the seven Islamic banks in Indonesia which published their annual reports for the period from 2011 to 2018 as its research sample. The analysis technique used in this study is a multiple regression analysis. Results: The results indicated that IA and CF competencies had a positive effect toward the sharia compliance of Islamic banks in Indonesia. Conclusion: It is necessary to enhance the competencies of IA and CF staff through improving their professional qualifications, such as through education programs, certification and relevant training on the scope of sharia supervision. Such actions need to be done to support IA and CF staff in performing the comprehensive supervision of sharia compliance.